Integrasi Nilai Bhinneka Tunggal Ika dalam Projek P5 pada Kurikulum Merdeka: Studi Kasus pada Mata Pelajaran IPS di SMPIT Misbahussudur Kota Depok - Hafidhah; Rugaiyah; Masduki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the implementation of the Bhinneka Tunggal Ika value in the Pancasila Student Profile Strengthening Project (P5) through Social Sciences (IPS) learning at SMPIT Misbahussudur, Depok City. Using a qualitative approach with a case study method, data was collected through interviews, observations, and analysis of curriculum documents. The results of the study indicate that the integration of diversity values ​​is effective when designed collaboratively, linked to the social context of students, and implemented through project-based learning. Activities such as local cultural exploration, cross-cultural dialogue, and student creative actions strengthen awareness of the importance of tolerance and unity in diversity. Despite challenges, such as limited resources and time, strategies such as teacher training and the use of digital media are able to support smooth implementation. IPS learning has proven to be a strategic medium in instilling the Bhinneka Tunggal Ika value contextually and meaningfully.